Cost-Effectiveness of Peer- Versus Venue-Based Approaches for Detecting Undiagnosed HIV Among Heterosexuals in High-Risk New York City Neighborhoods. (1st February 2018) - Stevens, Elizabeth R.; Nucifora, Kimberly A.; Zhou, Qinlian; Braithwaite, Ronald Scott; Cleland, Charles M.; Ritchie, Amanda S.; Kutnick, Alexandra H.; Gwadz, Marya V.
Abstract : Introduction: We used a computer simulation of HIV progression and transmission to evaluate the cost-effectiveness of a scale-up of 3 strategies to seek out and test individuals with undiagnosed HIV in New York City (NYC). Setting: Hypothetical NYC population. Methods: We incorporated the observed effects and costs of the 3 "seek and test" strategies in a computer simulation of HIV in NYC, comparing a scenario in which the strategies were scaled up with a 1-year implementation or a long-term implementation with a counterfactual scenario with no scale-up. The simulation combined a deterministic compartmental model of HIV transmission with a stochastic microsimulation of HIV progression, calibrated to NYC epidemiological data from 2003 to 2015. The 3 approaches were respondent-driven sampling (RDS) with anonymous HIV testing ("RDS-A"), RDS with a 2-session confidential HIV testing approach ("RDS-C"), and venue-based sampling ("VBS"). Results: RDS-A was the most cost-effective strategy tested. When implemented for only 1 year and then stopped thereafter, using a societal perspective, the cost per quality-adjusted life-year (QALY) gained versus no intervention was $812/QALY, $18, 110/QALY, and $20, 362/QALY for RDS-A, RDS-C, and VBS, respectively. When interventions were implemented long term, the cost per QALY gained versus no intervention was cost-saving, $31, 773/QALY, and $35, 148/QALY for RDS-A, RDS-C, and VBS, respectively. When compared with RDS-A, the incremental cost-effectiveness ratios for both VBS and RDS-C were dominated. Conclusions: The expansion of the RDS-A strategy would substantially reduce HIV-related deaths and new HIV infections in NYC, and would be either cost-saving or have favorable cost-effectiveness. Abstract : Supplemental Digital Content is Available in the Text.